Approach with initiative or hold on passively? The impact of customer-perceived dependence on customer forgiveness in service failure - Chen, Xin; Guo, Shuojia; Xiong, Jie; Hao, Shuyi (Frontiers in Psychology, 2022)
Service failure is almost inevitable with the intensifying competition in the service market and expectation of heterogeneous customers. The customer-firm relationship can significantly influence customers’ subsequent attitudes and behaviors to the service provider when they encounter service failure. This study proposes a theoretical model to examine how customer-perceived dependence affects their forgiveness toward a service failure in attribution logic. According to an experiment with 138 and a survey with 428 commercial bank customers, we used a multivariate approach to validate our model. The results show that relationship-valued dependence (RVD) leads to external attribution, which is positively related to customer forgiveness. In contrast, switching-cost dependence (SCD) leads to internal attribution, which is negatively related to customer forgiveness. The relationship length is a relevant contextual factor that acts as a negative moderating factor. Our study contributes to the service recovery literature by elucidating the underlying process of forgiveness with the presence of the customer-firm dependence relationship.